2016
DOI: 10.1021/acs.biomac.6b01247
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol) Crowding as Critical Factor To Determine pDNA Packaging Scheme into Polyplex Micelles for Enhanced Gene Expression

Abstract: A critical role of polyethylene glycol (PEG) crowding in the packaging of plasmid DNA (pDNA) into polyplex micelles (PMs) was investigated using a series of PEG-b-poly(l-lysine) (PEG-PLys) block copolymers with varying molecular weights of both PEG and PLys segments. Rod-shaped PMs preferentially formed when the tethered PEG chains covering pDNA in a precondensed state were dense enough to overlap one another (reduced tethering density (RTD) > 1), whereas globular PMs were obtained when they were not overlappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 33 publications
3
56
0
Order By: Relevance
“…95 In this manner, the degree of PEGylation and density of PEG on the surface of these carriers can lead to modifications in the protein corona and accordingly the interactions of the carriers with cells in biological environments. [96][97][98][99] Although PEG conjugation has led to various successes with providing stability and increasing circulation time, PEGylation could impact the activity of the active drug by changing its con-formation, causing steric hindrance and altering electrostatic binding properties. 100 Further, the possibility of inducing production of anti-PEG IgM antibodies could lead to rapid elimination and enhanced hepatic uptake of a second dose of the PEGylated carrier.…”
Section: Influence Of Charge On Protein Corona Formationmentioning
confidence: 99%
“…95 In this manner, the degree of PEGylation and density of PEG on the surface of these carriers can lead to modifications in the protein corona and accordingly the interactions of the carriers with cells in biological environments. [96][97][98][99] Although PEG conjugation has led to various successes with providing stability and increasing circulation time, PEGylation could impact the activity of the active drug by changing its con-formation, causing steric hindrance and altering electrostatic binding properties. 100 Further, the possibility of inducing production of anti-PEG IgM antibodies could lead to rapid elimination and enhanced hepatic uptake of a second dose of the PEGylated carrier.…”
Section: Influence Of Charge On Protein Corona Formationmentioning
confidence: 99%
“…Notably, single DNA condensation is guaranteed when the complexation proceeds in dilute conditions. For example, in a complex of pDNA and PEG-b-P(Lys) block copolymer, single DNA packaging proceeds when the pDNA concentration is at most 0.35 mg/mL; otherwise, the polyplexes form a network involving multiple DNA [40]. This is because the formation of the PEG shell must be completed before surrounding DNA complexes collide due to translation motion.…”
Section: Single-dna Condensation Regulated By Copolymersmentioning
confidence: 99%
“…Similarly, in PMs made from PEG-g-Cysteine-P(Lys) with the DP of the P(Lys) block fixed at 30, the rod length increased when the molecular weight of PEG was increased [46]. The globular structure dominated when the DP of the polycation block was relatively higher and that of the hydrophilic block was relatively lower, such as in the cases of PEG 2kDa -b-DMAEMA 100 and PEG 2kDa -b-P(Lys) 100 [40,49]. Collectively, these observations indicated that as the DP of the polycation block increases, the rod length decreases and the formation of the globular structure becomes more frequent.…”
Section: Globular Rod-shaped and Toroidal Structuresmentioning
confidence: 99%
“…Still, the degree of PEGylation on the nano-biointerface as well as PEG density can modify the protein corona and its NC performance under biological conditions. For instance, Kataoka and co-workers recently showed that tethered PEG density with highly squeezed PEG chains on the interface of pDNA-polyplexes assured higher circulation properties to improve pDNA delivery ( 54 , 55 ). For site-specific targeting of NC with ligands to manage selective interaction with the ligand-corresponding receptor, PEGylation is often the only way to reduce additional uncontrolled protein corona formation, which would counteract with the targeting groups ( 56 ).…”
Section: The Protein Corona Around Nc As a Confounding Variable For Ementioning
confidence: 99%